Pengembangan Aplikasi Deteksi Stunting di Kelurahan Duren Sawit - Nur Hikmah; Herry Wahyono; Herwanto, Herwanto; Nuke L Chusna; Adam Elvandi Yusup (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Stunting is a condition in which toddlers experience a lack of nutritional intake for a long period of time so that children experience growth disorders, namely their height is shorter than the age standard. This community service activity was carried out in the Duren Sawit Village. Based on the results of the team's interviews with related parties, so far the process of recording and monitoring children's growth and development data is still done manually. For this reason, an application was developed that is expected to help and facilitate related parties in recording and monitoring child growth and development data. In addition, this application is also expected to be able to provide a visualization of the condition of child growth and development in an area through the process of early detection of stunting on child growth and development data that is inputted at the time of measurement. Bootstrap is a CSS framework that is most in demand by website developers. By using bootstrap we can easily design a responsive website appearance. For this reason, a stunting detection application was made using the bootstrap framework, with the aim that users can more easily use and access this stunting detection application.